Modelling of Lithium ion battery using method of lines technique / Rahifa Ranom … [et al.] - Ranom, Rahifa; Yusof, Norzihani; Abd Rahim, Noorafiqah; Ahmad Jamal, Saidatul Nur Aisyahtun Sakinah (Division of Research and Industry Linkages, 2017)
The modeling of Lithium ion battery involves a large and complex multi scale system measuring from the microscopic system (electrode particles) to that of the macroscopic system (the length of the cell). Furthermore, the time derivative o f diffusion-advection model o f charge transport is coupled with an ordinary differential equation (ODE) of potential equation. Therefore, solution to such model requires an efficient and a versatile method namely Method of lines technique (MOL). The MOL is a numerical technique that converts the PDEs into a set of ODEs in the time variable through discretisation process of spatial derivatives using finite difference scheme. The ODEs are then being solved using a built-in ODE solver. The potential discharge curve is compared to an experimental data of half-cell LiFEP04 cathode. It is shown that the technique provides high accuracy solution to the system, numerical stability and computational efficiency.